Social Support, Religiosity, and Health Literacy as Predictors of Resilience in Pregnant Women during COVID-19 Pandemic - Nora Devi Irianjani; Elli Nur Hayati; Ma Teresa De Guzman (Universitas Ahmad Dahlan, 2022)
Being pregnant during pandemic is challenging for women. A long and uncertain pandemic condition is accompanied by changes in health services, and other life conditions that require adaptation, coping, and resilient. Â This study aimed to examine the role of social support, religiosity, and health literacy as predictors of resilience among pregnant women during the COVID-19 pandemic in Yogyakarta, Indonesia. A purposive random sampling was employed to select participants of the survey, which was pregnant women that attended in antenatal care in Primary Health Care in Yogyakarta region.Â Â The scales of resilience, social support, religiosity, and health literacy was carried out to collect the data. Results showed that social support has a more significant contribution than health literacy and religiosity on resilience of pregnant women. Overall, there is a suitable health literacy mediation model between social support and resilience and religiosity with resilience. Social support, health literacy, and religiosity can be the predictors of resilience.